L'ordre à Louisbourg : mesures de contrôle dans une société coloniale française, 1713-1758 - Johnston, A. J. B (2018)
Between 1713 and 1758, there was a major French colonizing venture on Cape Breton Island. The colony was known as Ile Royale and its principal settlement and administrative centre was Louisbourg. A multitude of controlling measures were introduced throughout the lifespan of the colony so as to make the society as ordered as possible. Most initiatives arose in and were directed at the capital, Louisbourg. The outport settlements were left largely to their own, informal means when it came to questions of order and control. The impetus to make Louisbourg an ordered society was deeply rooted in colonial officials, and to a lesser extent in the colonists themselves. Virtually every sphere of public life, and some aspects of private life, were touched by controlling measures. Some of the more prominent controls were in the following areas: town planning and the organization of space within the intra muros at Louisbourg; public celebrations, especially those which promoted the monarchy and the hierarchical values underpinning it; ordinances and practices aimed at discouraging certain types of behaviour; and the use of exemplary punishments in a formal justice system. The efforts to create an ordered society at Louisbourg were in keeping with patterns found in contemporary France and New France. Yet the distinctive economic, social and demographic situations in the capital of He Royale posed special challenges. There was a prolonged imbalance in the sexes, a population mix which was more diverse than was usually the case in New France, and there were a large number of transients in port throughout the shipping season. Moreover, the military presence at Louisbourg was so large, between one quarter and one-half of the population, that there were many possibilities for friction between the civil and military spheres of colonial society. The defensive needs of the place were such that military requirements had a considerable impact on life in the town: from how the grid took shape to how and when people were allowed to ...